Wasiat HB IX Yogyakarta Kota Republik Haryadi Baskoro & Sudomo Sunaryo ; penyunting, Antonius Sigit Suryanto. - HARYADI BASKORO; Antonius Sigit Suryanto; Sudomo Sunaryo (Galang Press, 2011)
241 hlm. ilus. 23 cm (3 eks.)